Theoretical Analysis of Gap Coupled Microstrip Patch Antenna - Akanksha Gupta; D K Srivastava; J.P. Saini (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
When a patch is placed close to the fed patch, get excited due to parasitic coupling between the two elements. This proposed work presents theoretical analysis of rectangular gap coupled microstrip patch antenna (R-GCMSA) using circuit concept model, and the effect of gap(g), feed width (Wf), and feed length on performance of the impedance bandwidth is also studied, it is observe as the gap between the parasitic element is increased resonant frequency shifted towards the parasitic patch resonant frequency for broadening the impedance bandwidth. The maximum impedance bandwidth for the proposed antenna design is 12.7% in the frequency range of 3.24-3.7GHz measured, with rectangular shape ground plane size 6030m.m2.the highest directivity achieved is 4dBi.The proposed design is simple in structure and compact in size, proposed design is simulated on IE3D Microwave simulator, the simulated result is in good agreement with obtained theoretical and measured results.